Mining Dependency, Public Expenditure, and Regional Economic Structural Transformation in Central Sulawesi Province - Marselius Fransiskus Talahatu (Jurnal Ekonomi Pembangunan, 2026)
This study analyzes the effect of dependence on the mining sector and regional public spending on the process of economic structural transformation at the district/city level using panel data from 13 districts/cities in Central Sulawesi Province during the period 2013–2023. The analysis was conducted using a two-way Fixed Effects model with cluster-robust standard errors to control for differences in regional characteristics and intertemporal changes. The results show that dependence on the mining sector has a negative and significant effect on non-mining economic performance per capita (β = −3.36; p < 0.01). This finding indicates the existence of structural pressures arising from the dominance of the extractive sector at the regional level. Population size, as a proxy for economic agglomeration, has a positive and significant effect (β = 1.91; p < 0.01), reflecting the role of economies of scale in strengthening non-mining activities. The public expenditure variable shows an economically relevant coefficient direction. The interaction model shows that capital expenditure has the potential to mitigate the negative impact of mining dependence, but the effect is marginal (p < 0.10). The results of this study confirm that regions that depend on the mining sector tend to face obstacles in strengthening their non-mining economic base. A reorientation of public expenditure that is more productive and focused on developing the non-extractive sector is needed to support the regional structural transformation process